Cultural elements and its classification in the Quran: a thematic analysis - A. Bakar, Arnida; Ramli, Sulhah; Abd. Rahman, Akmal Khuzairy (Universiti Sains Islam Malaysia, Persatuan Penterjemah Malaysia, Dewan Bahasa dan Pustaka, Institut Terjemahan dan Buku Malaysia, 2019)
The study attempts to categorize cultural elements in the Quran using the thematic approach. The study found that cultural elements in the Quran fall generally into two categories namely the material and the conceptual.